2020
DOI: 10.1186/s43161-020-00001-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of forward head and rounded shoulder posture on hand grip strength in asymptomatic young adults: a cross-sectional study

Abstract: Background: Forward head and rounded shoulder posture (FHRSP) is a common clinical postural misalignment. It leads to flexion posture of the spine which increases the amount of tension on the nerve roots, which inversely affects muscle strength and function of the upper extremity. So, this study was conducted to examine the effect of FHRSP on hand grip strength in asymptomatic young adults and to explore the relationship between the craniovertebral angle (CVA) and hand grip strength. Results: There was no sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…There is an increase in tension on the nerve roots, affecting muscle strength [16]. There is an alteration in the mechanical properties of the muscles, which include the stiffness, elasticity, and changes in the cervical regions [17]. Clinically, it is noted that the non-specific neck pain has not reported problems with the upper limb functions.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increase in tension on the nerve roots, affecting muscle strength [16]. There is an alteration in the mechanical properties of the muscles, which include the stiffness, elasticity, and changes in the cervical regions [17]. Clinically, it is noted that the non-specific neck pain has not reported problems with the upper limb functions.…”
Section: Discussionmentioning
confidence: 99%
“…These inconclusive results may be attributable to the fact that these studies have focused on the effect of head/neck position, not the structural postural deviation of the head, on hand grip strength and because they have included asymptomatic young adults. In the only study that examined the effect of FHP on hand grip strength, Mosaad et al reported no difference in hand grip strength between young adults with and without FHP [ 35 ]. This may arise from the small mean difference (~ 8 0 ) in the CVA between groups with and without FHP, that is, the severity of the head postural deviation was insufficient to cause distal alternations in the upper extremity.…”
Section: Discussionmentioning
confidence: 99%
“…Longer rest positions when using a computer, smartphone, or other media exposes individuals to greater risk factors and increase the incidence of forward head posture (FHP) 1 . One research determined that FHP most happens in employees, adolescents, and students 2. According to the prevalence of common faulty postures among individuals, the most prevalent faulty postures were unequal shoulder degree (36%) and forward head position (25%) 3 . The individuals are regularly uncovered to the repetitive movements of the body that are hazardous for growing musculoskeletal symptoms.…”
Section: Introductionmentioning
confidence: 99%